Human Melanocyte-Derived Spheroids: A Precise Test System for Drug Screening and a Multicellular Unit for Tissue Engineering - Zurina, Irina M.; Gorkun, Anastasiya A.; Dzhussoeva, Ekaterina V.; Kolokoltsova, Tamara D.; Markov, Dmitriy D.; Kosheleva, Nastasia V.; Morozov, Sergey G.; Saburina, Irina N. (Frontiers in Bioengineering and Biotechnology, 2020)
Pigmentation is the result of melanin synthesis, which takes place in melanocytes, and its further distribution. A dysregulation in melanocytes’ functionality can result in the loss of pigmentation, the appearance of pigment spots and melanoma development. Tissue engineering and the screening of new skin-lightening drugs require the development of simple and reproducible in vitro models with maintained functional activity. The aim of the study was to obtain and characterize spheroids from normal human melanocytes as a three-dimensional multicellular structure and as a test system for skin-lightening drug screening. Melanocytes are known to lose their ability to synthesize melanin in monolayer culture. When transferred under non-adhesive conditions in agarose multi-well plates, melanocytes aggregated and formed spheroids. As a result, the amount of melanin elevated almost two times within seven days. MelanoDerm (MatTek) skin equivalents were used as a comparison system. Cells in spheroids expressed transcription factors that regulate melanogenesis: MITF and Sox10, the marker of developed melanosomes – gp100, as well as tyrosinase (TYR) – the melanogenesis enzyme and melanocortin receptor 1 (MC1R) – the main receptor regulating melanin synthesis. Expression was maintained during 3D culturing. Thus, it can be stated that spheroids maintain melanocytes’ functional activity compared to that in the multi-layered MelanoDerm skin equivalents. Culturing both spheroids and MelanoDerm for seven days in the presence of the skin-lightening agent fucoxanthin resulted in a more significant lowering of melanin level in spheroids. Significant down-regulation of gp100, MITF and Sox10 transcription factors, as well as 10-fold down-regulation of TYR expression, was observed in spheroids by day 7 in the presence of fucoxanthin, thus inhibiting the maturation of melanosomes and the synthesis of melanin. MelanoDerm samples were characterized by significant down-regulation of only MITF, Sox10 indicating that spheroids formed a more sensitive system allowed for quantitative assays. Collectively, these data illustrate that normal melanocytes can assemble themselves into spheroids – the viable structures that are able to accumulate melanin and maintain the initial functional activity of melanocytes. These spheroids can be used as a more affordable and easy-to-use test system than commercial skin equivalents for drug screening.